Protective effect of maternal exercise against amyloid-β neurotoxicity in the male rat offspring's cerebellum. (23rd October 2020) - Klein, Caroline Peres; Hoppe, Juliana Bender; Saccomori, André Brum; Gindri dos Santos, Bernardo; August, Pauline Maciel; Klein, Isadora Peres; Crestani, Mariana Scortegagna; Bifi, Felippo; Hözer, Régis Mateus; Navas, Plácido; Salbego, Christianne Gazzana; Matté, Cristiane
Abstract: The Developmental Origins of Health and Disease (DOHaD) states that intrauterine maternal environment influences postnatal life by programming offspring's metabolism. Intrauterine milieu induced by exercise during pregnancy promotes long-lasting benefits to the offspring's health and seems to offer some resistance against chronic diseases in adult life. Alzheimer's disease is a public health concern with limited treatment options. In the present study, we assessed the potential of maternal exercise during pregnancy in long-term programming of young adult male rat offspring's cerebellar metabolism in conferring neuroprotection against amyloid-β (Aβ) neurotoxicity. Female Wistar rats were submitted to a swimming protocol 1 week prior mating and throughout pregnancy (five sessions/a week lasting 30 min). Aβ oligomers were infused bilaterally in the brain ventricles of 60-day-old male offspring. Fourteen days after surgery, we measured parameters related to redox state, mitochondrial function, and the immunocontent of proteins related to synaptic function. We found that maternal exercise during pregnancy attenuated several parameters in the offspring's male rat cerebellum, such as the reactive species rise, the increase of inducible nitric oxide synthase immunocontent and tau phosphorylation induced by Aβ oligomers, increased mitochondrial fission indicated by dynamin-related protein 1 (DRP1), and protein oxidation identified by carbonylation. Strikingly, we find that maternal exercise promotes changes in the rat offspring's cerebellum that are still evident in young adult life. These favorable neurochemical changes in offspring's cerebellum induced by maternal exercise may contribute to a protective phenotype against Aβ-induced neurotoxicity in young adult male rat offspring.